Sexual education as a tool to prevent sexually transmitted infections in the elderly: an integrative review (Research, Society and Development, 2023)
Objective: To describe how the literature approaches sexual education as a way to prevent sexually transmitted infections in the elderly population. Methodology: This is an integrative review of the literature, with a qualitative approach and a descriptive character. The search was carried out on the online platforms: VHL and CAPES Journal. The selected articles were published in Portuguese and English, published from 2015 to 2022, being used as descriptors: sex education, sexually transmitted diseases and aged. Results: In recent years, there has been an increase in STIs in the elderly, where the scarcity of information, social stigmas and the unpreparedness of health professionals in the care of this population are the main drivers of the problem. Moreover, it was noted that the training of health professionals and the realization of educational practices are strategies used to deconstruct taboos related to sexuality in the elderly, health promotion and prevention of STIs. Conclusion: The studies reveal the increase in STIs in the elderly, with this it is notorious the importance of updating the health team and the adoption of educational practices for the elderly, in order to provide safe information about sexual practice, disprove the current taboos and improve the health care provided to this population.